Different Traditional Herbal Medicines for the Treatment of Gastroesophageal Reflux Disease in Adults - Dai, Yun-kai; Wu, Yun-bo; Wen, Hao; Li, Ru-liu; Chen, Wei-jing; Tang, Chunzhi; Lu, Liming; Hu, Ling (Frontiers in Pharmacology, 2020)
Background/Aims Traditional Herbal Medicines (THM) have been being used for gastroesophageal reflux disease (GERD) for a long time, but clinical evidence is still scarce. We evaluated different THM prescriptions for GERD in adults. Methods Data added to nine online databases from their inception to November 30, 2019, were systematically searched. All relevant randomized controlled trials (RCTs) were included and were combined with Bayesian network analysis. The Cochrane Collaboration’s risk of bias tool and GRADE profiler version 3.6 were respectively employed to evaluate the quality of evidence of outcomes. Results Seventeen publications involving 1441 participants were retrieved. The results of our analysis suggested that Jianpi therapy+proton pump inhibitors (PPIs) and Ligan Hewei therapy respectively ranked first in overall clinical efficacy and efficacy under gastroscope; Ligan Hewei therapy+PPIs was the optimum intervention in the improvement of acid regurgitation and heartburn. Conclusion This research indicates that Ligan Hewei therapy and Jianpi therapy, or these therapies separately combined with PPIs, should be recommended as appropriate complementary and alternative treatments based on the specific characteristics of GERD. However, additional well-designed RCTs with high methodological quality are still needed for future research.